Assessment of a railway concrete arch bridge by numerical modelling and measurements - He, Guojing; Zou, Zhongquan; Enochsson, Ola; Bennitz, Anders; Elfgren, Lennart; Kronborg, Anders; Töyrä, Björn; Paulsson, Björn (Luleå tekniska universitet, Byggkonstruktion och brand, 2008)
Two main railway concrete arch bridges have been investigated in northern Sweden: the Vindel Bridge over the Vindel River with a span of 110 m and the Långforsen Bridge over the Kalix River with a span of 90 m. The bridges were constructed in the 1950s with similar designs. In order to investigate the possibility to increase the axle load from 225 kN to 250kN, two 3-D Finite Element models with shell elements were developed and two field tests were carried out with passing trains and ambient vibrations. The measurement frequencies and mode shapes were studied with the stochastic subspace identification method in the time domain. Based on a comparison of the predictions of the FE analyses and the results of the field tests, the FE models were updated. It was found that it was possible to make good predictions of the actual dynamic response with reasonable assumptions of material properties and joint stiffness in the structure. ISBN för värdpublikation: 978-0-415-46844-2